KONY 2012: Branding the Enemy—Activism Imagery in the Age of Social Media and the Political Brand. Issue 1 (2nd January 2016) - Shirley, Adam Trey
ABSTRACT: The KONY 2012 campaign, released by Invisible Children in early March 2012, is a carefully strategized program of destruction through promotion (aimed at destroying Joseph Kony's image while making him famous). It is composed of a series of branded visual identity images, logos, text, and videos that are currently rewriting contemporary strategies for generating activism through social media. This article investigates the visual imagery and media of the KONY 2012 campaign and considers how the campaign team purposefully creates a subversive brandspace where individuals interact with the preformulated anti-Kony imagery that aids in the construction, communication, and maintenance of an antipathetic political brand identity. It also considers the implications of the iconoclastic visual rhetoric used by campaign designers to encourage the symbolic destruction of Kony's image by making him notoriously iconic. Finally, it investigates the religious undertones of the campaign and its selective recruitment of followers through evangelical churches and organizations.